Albite ± Actinolite-Altered Porphyry Dykes in Archean Gold Deposits of the Boulder Lefroy-Golden Mile Fault System, Yilgarn Craton, Western Australia: Petrography, Chronology, and Comparison to Canadian Albitites - Andreas G. Mueller (MDPI AG, 2021)
The Boulder Lefroy-Golden Mile fault system in the Archean Yigarn Craton is the most productive gold-mineralized structure in Australia (>2300 t Au). The New Celebration deposit (51 t Au) is part of a group of hematite- and anhydrite-bearing mesothermal deposits and Fe-Cu-Au skarns associated with monzodiorite-tonalite intrusions in the strike-slip fault system. Ore-grade biotite-carbonate and late sericite-carbonate-alkali feldspar replacement is bound to the contacts of a felsic (low Cr, Ni, V) quartz-plagioclase porphyry dyke dated at 2676 ± 7 Ma. The sodic-potassic alteration of the felsic boudinaged dyke contrasts with the albite-actinolite alteration in the adjacent mafic (high Cr, Ni, V) plagioclase porphyry dated at 2662 ± 4 Ma, although both share the same sulfide-oxide assemblage: pyrite ± chalcopyrite, magnetite ± hematite. The younger porphyry locally crosscuts foliation and is bordered by post-kinematic actinolite-pyrite selvages overprinting talc-chlorite-phlogopite-dolomite schist. It contains auriferous pyrite (70 ppb Au; 610 ppb Ag) where sampled for zircon U-Pb chronology at +224 m elevation. Above the sample site, the dyke was mined as gold ore (1–6 g/t Au) at +300–350 m. Temperature estimates based on actinolite-albite pairs (300–350 °C) agree with the fluid inclusion trapping temperature of main-stage auriferous veins (330 ± 20 °C). These relationships are interpreted to indicate syn-mineralization emplacement. Gold-related albite-altered porphyry dykes (albitites) also occur in the world-class Hollinger-McIntyre (986 t Au) and Kerr Addison-Chesterville deposits (336 t Au), Abitibi greenstone belt, Canada.